Detecting aromatic compounds on planetary surfaces using ultraviolet time-resolved fluorescence spectroscopy. (February 2018) - Eshelman, E.; Daly, M.G.; Slater, G.; Cloutis, E.
Abstract: Many aromatic organic molecules exhibit strong and characteristic fluorescence when excited with ultraviolet radiation. As laser excitation in the ultraviolet generates both fluorescence and resonantly enhanced Raman scattering of aromatic vibrational modes, combined Raman and fluorescence instruments have been proposed to search for organic compounds on Mars. In this work the time-resolved fluorescence of a suite of 24 compounds composed of 2–5 ringed alternant, non-alternant, and heterocyclic PAHs was measured. Fluorescence instrumentation with similar specifications to a putative flight instrument was capable of observing the fluorescence decay of these compounds with a sub-ns resolution. Incorporating time-resolved capabilities was also found to increase the ability to discriminate between individual PAHs. Incorporating time-resolved fluorescence capabilities into an ultraviolet gated Raman system intended for a rover or lander can increase the ability to detect and characterize PAHs on planetary surfaces. Highlights: A time-resolved (TR) laser-induced fluorescence study of 24 PAHs is performed. The 266 nm excitation instrument is practical for future in-situ Mars exploration. The study quantitatively shows the improved identification of PAHs using TR. This capability is recommended for future spaceflight instruments.